Analysis Pork Contamination in Beef Meatballs through Polymerase Chain Reaction in Palu City - Tresya J. Polibaon; Mariyani; Joni Tandi; Tien Wahyu Handayani; Rahmawati Salsa Dinurrosifa; Ikhsan Hi. Amir Sene (Postgraduate, University of Mataram, 2024)
The need for halal products is essential, particularly among various processed beef products like meatballs, which are popular among nearly the entire community. These products are susceptible to issues of meat counterfeiting for greater economic gain. This study aims to determine the smallest DNA concentration that can still be detected and to assess whether there is any pork contamination in meatballs circulating in Palu City using Polymerase Chain Reaction (PCR). This test uses four DNA samples obtained from fresh meat to test the specificity of the primer: wild boar, rat, and goat DNA samples as comparisons, and pig DNA as a positive control. The presence of DNA bands in the agarose gel electrophoresis visualization results indicates that DNA amplification has occurred, meaning that the sample can be detected. The analysis results showed that the primer used (Cyt-b) had good specificity for detecting pork DNA, while the absolute pork DNA concentration of 0.01 ng/µL and the reference meatball DNA with a concentration of 0.01% are the smallest limits that can still be detected using PCR. Of the four meatball samples from Palu City, one sample produced a DNA band, indicating that the sample contains or is contaminated with pig DNA. This method is valid as it meets the specificity test and demonstrates a good detection limit.